Optimizing the Policy for Implementing the Guidance and Supervision Function of Marriage Requirements by Strengthening the Capacity of KUA Resources - Felna Mustapa (POKJANAS Bekerja Sama Biro Perencanaan dan Penganggaran, Sekretariat Jenderal Kementerian Agama RI, 2026)
The implementation of the guidance and supervision function for marriage requirements at the Office of Religious Affairs (KUA) currently faces serious challenges that have implications for the validity of marriage legality and family resilience in Indonesia. This policy research aims to formulate strategies to optimize the KUA's function by strengthening human resource capacity to address weak document verification and the low quality of premarital guidance. The policy methodology used is a descriptive qualitative approach with Policy Research analysis methods, involving the study of regulatory documents, field observations, and descriptive analysis of secondary data on divorce rates and marital status disputes. The analysis was conducted by identifying gaps between the standard operating procedures stipulated in the regulations and the reality of technical capacity at the sub-district level. The study results indicate that the main factors contributing to weak supervision are an imbalance in the ratio of the number of registrars to their workload, a lack of digital literacy among officers in detecting data manipulation, and a fluctuating guidance budget. Consequently, the KUA's function is often reduced to merely an administrative recording institution rather than a guardian of the quality of family law.